Material didáctico: una aproximación desde el aprendizaje decolonial de la cultura Azteca para sexto grado. (2024)
This degree project carries out qualitative research framed in an interpretive paradigm (Vasilachis, 1992; Krause, 1995). The first phase integrates the review of literature and the creation of a didactic primer on Moctezuma and the Aztec civilization, seeking to create decolonial preconceptions in sixth-grade students of the Santa Marta I.E.D. public school from Bogotá, Colombia. The sample includes boys and girls from 9 to 11 years old.